225k views
2 votes
X + 3y = −4 x + 5y = −6

User Wch
by
5.1k points

1 Answer

5 votes

For this case we must solve the following system of equations:


x + 3y = -4\\x + 5y = -6

We clear x of both equations:


x = -4-3y\\x = -6-5y

We match:


-4-3y = -6-5y\\-3y + 5y = -6 + 4\\2y = -2\\y = \frac {-2} {2}\\y = -1

We find the value of "x":


x = -4-3 (-1)\\x = -4 + 3\\x = -1

Thus, the solution of the system is:


(x, y): (- 1, -1)

Answer:


(x, y): (- 1, -1)

User Adam Porad
by
6.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.